Efektivitas Penanganan Premanisme di Kecamatan Pampangan Kabupaten Ogan Komering Ilir - Jonson, Jonson; Sutinah, Sutinah; Mayreista, Dita (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
In order to prevent thuggery from occurring so that it does not cause commotion or disturb public comfort, security and order requires good handling from the police, because the police is a government agency that is needed by the government to handle cases of thuggery, hopefully the police can handle it. The efforts that have been made by the Pampangan Ogan Komering Ilir Sector Police in dealing with acts of thuggery in Ogan Komering Ilir Regency, especially in the Pampangan area, include: The role of all related parties, namely: Community Leaders, Ulama, Government and Police, Kamling Post, Routine Operations, Patrolling certain areas where thuggery activities regularly occur and monitoring areas. The aim of this research is to analyze the effectiveness of handling thuggery in Pampangan District, Ogan Komering Ilir Regency. The problems identified are: The number of personnel is not proportional to the population in Pampangan District, the lack of community to fully participate in handling crime, and the lack of response to the commission of crimes because they believe that this will happen, which is still within normal limits which does not cause too much harm. losses, limited funds/budget in the process of investigating a criminal act during its commission and lack of socialization regarding thuggery which greatly disturbs the safety and comfort of other people as well. Qualitative analysis techniques used in this research. This research shows that: overall the handling of thuggery is effectively implemented in Pampangan District, Ogan Komering Ilir Regency. Although in its implementation there are still obstacles, including: The number of personnel is not proportional to the population in the Pampangan area, full community participation in crime prevention, and a lack of response capacity when a crime occurs because they still consider this to be a reasonable limitation and not cause too much loss. large, limited funds/budget in the investigation process at the time of the crime and lack of socialization regarding acts of thuggery, that such acts really disturb security, comfort and will harm other people, and will break friendships.